The Investigation of Thermodynamic and Structural Parameters in Cu-Al-Fe-Mn SMAs - Aziz Baiz, Sivar; Aksu Canbay, Canan; Ozkul, Iskender (Amer Inst Physics, 2018)
Among SMAs, Cu-based SMAs have the lowest production cost. In this study, Cu-Al based SMA with a new composition were fabricated by arc melting. After the homogenization of the specimen by solution-treatment, differential calorimetry analysis (DSC) measurements were made. The characteristic transformation temperatures of the alloy samples were determined and some thermodynamic parameters were calculated by using the DSC results. The high temperature transitions and the eutectoid points of the alloy samples were investigated with DTA measurements. The structural X-ray investigation results of the samples showed the martensitic formations occurred in the alloy sample for their diffraction patterns were referred to the typical martensite planes. The grain size and valence electron concentration values were also calculated. In the optical micrographs of the samples, the martensite forms inside the grains were able to seen in different directions and these supported to the results of the other measurements.
34th International Physics Congress (IPS) of the Turkish-Physical-Society (TPS) -- SEP 05-09, 2018 -- Konacik, TURKEY
Keywords: Shape-Memory Alloys